A full-scale field study on mitigation of environmental ground vibrations by using open trenches. (October 2021) - Toygar, Onur; Ulgen, Deniz
Abstract: Environmental ground vibrations induced by construction operations, machine foundations, vehicular and railway traffic may cause discomfort to the dwellers in their immediate vicinity and malfunctioning of sensitive equipment in nearby structures. Associated with technological development and rapid industrialization, undesired vibrations around the residential areas have increased. Hence, the isolation of those vibrations has become an important issue. Open trenches are mainly employed as wave barriers in mitigation of undesired vibrations. Recent studies have focused on the parameters affecting the vibration isolation performance of open and in-filled trenches. It is stated that screening effectiveness mainly depends on the type of the vibration source and geometric dimensions of open trenches along with the local site conditions. In the present study, a series of full-scale field experiments were conducted to identify the effects of governing parameters on efficiency. The amplitudes of ground vibrations, artificially generated on the site, were measured through highly sensitive accelerometers at different test configurations. It was concluded that the frequency of vibrations had more influence than the actual depth of the barrier on screening effectiveness. Better isolation can be achieved in a region close to the trench while the effectiveness decreases at great distances. In addition, the results were compared with those of recently reported in experimental studies. Highlights: Environmental vibrations may cause adverse effects on structures and dwellers. Isolation of environmental ground-borne vibrations by open trench. Isolation performance of open trench was quantitatively obtained by field tests. The effects of actual trench depth and source location were investigated. The source frequency generally governs the isolation performance of wave barriers.